Risk factors for mortality caused by hypothalamic obesity in children with hypothalamic tumours. Issue 5 (14th October 2015) - Haliloglu, B.; Atay, Z.; Guran, T.; Abalı, S.; Bas, S.; Turan, S.; Bereket, A.
Summary: Background: Hypothalamic obesity (HyOb) is a common complication of childhood hypothalamic tumours. Patients with HyOb probably have a higher mortality rate than those with other types of obesity due in many cases to obstructive sleep apnoea/hypoventilation. Objectives: To identify predictive factors for mortality caused by HyOb in children. Methods: Twenty children with HyOb secondary to hypothalamic tumours that were followed‐up for ≥3 years and aged <15 years at diagnosis, and received supraphysiological glucocorticoid treatment for ≤1 month. Results: Mean age at diagnosis was 6.36 ± 3.60 years. Mean body mass index (BMI) Standard deviation of the samples (SDS) increased from 0.77 ± 1.26 to 2.66 ± 1.45 during the first 6 months, but slowed from month 6–12 (2.73 ± 1.35). ΔBMI SDS at 0–6 months was significantly higher in patients aged <6 years at diagnosis than in those aged >6 years at diagnosis (3.71 ± 1.96 vs. 0.83 ± 0.73, P  < 0.001). Maximum BMI SDS was also significantly higher in the younger group (3.88 ± 1.39 vs. 2.79 ± 0.64, P  < 0.05). In all, four patients died and the mortality rate was significantly higher in the patients with a further increase in BMI SDS > 1 SDS after 6 months of therapy (RR: 8.4, P  < 0.05). Both overall mortality and obesity‐related mortality rates were higher in the patients aged <6 years at diagnosis (4.5‐fold, 7.2‐fold higher, respectively, P  > 0.05). The mortality rate was also 3.7‐fold higher in the patients with a maximum BMI SDS ≥ 3 at any time during the first 3 years after therapy( P  > 0.05). Conclusions: An increase in BMI SDS after 6 months of therapy was observed to be a risk factor for mortality caused by HyOb. In addition, age <6 years at diagnosis and a maximum BMI SDS ≥ 3 were associated with a higher mortality rate, indicating that earlier and more aggressive treatment of obesity is required.